If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -1(7x + 15) = 13 + -3x Reorder the terms: 2 + -1(15 + 7x) = 13 + -3x 2 + (15 * -1 + 7x * -1) = 13 + -3x 2 + (-15 + -7x) = 13 + -3x Combine like terms: 2 + -15 = -13 -13 + -7x = 13 + -3x Solving -13 + -7x = 13 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -13 + -7x + 3x = 13 + -3x + 3x Combine like terms: -7x + 3x = -4x -13 + -4x = 13 + -3x + 3x Combine like terms: -3x + 3x = 0 -13 + -4x = 13 + 0 -13 + -4x = 13 Add '13' to each side of the equation. -13 + 13 + -4x = 13 + 13 Combine like terms: -13 + 13 = 0 0 + -4x = 13 + 13 -4x = 13 + 13 Combine like terms: 13 + 13 = 26 -4x = 26 Divide each side by '-4'. x = -6.5 Simplifying x = -6.5
| 4(x-3)=10x+24 | | x/y=13/5 | | 14x+6=2(5+7)-4 | | y=500x+200 | | 8x=8x+46 | | (7a+9b+8)+(a-b+1)= | | -2-8+a=116 | | -2x^2-3x+18= | | 5x+4=8x+3 | | -70=4(a+1)-6(6a+7) | | -6=8/x | | 6u^2-10u^5v^4/6u^3y^6 | | 8x-8+3a=5ax-2a | | n/-3.2=1.6 | | 4x+24=3x+4 | | 4c+5=z-4 | | -(-6n+6)-4(1+5n)=18 | | -5x-13=38 | | 3x+2x-6=26 | | 8+-10=6 | | 11y+77=31y+62 | | 3/10x-15 | | 4m+5-3m=x | | 1/3y=1/6 | | 280^1/2 | | 24+n=19 | | 1x+5=x-7 | | 7+5s-6=7s+7-5s | | 3-12y=7y+7 | | 4/5x-48 | | (w^9)^(1/3) | | (-6)+3.98= |